(untitled) (Bangladesh Critical Care Journal, 2013)
Objective: Worldwide cardiac cases constitute a large portion of the medical emergencies. There is a paucity of data on the prevalence of cardiac emergencies in Bangladesh. The purpose of this study was to identify the pattern of presentation of cardiac emergencies in a tertiary care hospital in Bangladesh. Methods and Materials: A hospital based cross sectional study was carried out at a medical college hospital in Dhaka city. Hospital medical records of 2457 patients admitted in the Coronary Care Unit (CCU) between 1 July 2011 to 30 June 2012 were reviewed. Relevant socio demographic data were abstracted from the hospital record files. Result: About 4.5% of the total emergency hospital admission was on the CCU. The mean age of the admitted pateints was 55.5 (SD 9.56) years. Males were affected twice as females. Majority of the patients presented with Acute Myocardial Infarction (AMI) (42%), followed by Acute Left Ventricular Failure (19%) and Unstable Angina (16%). Small portion of the patients admitted with Cardiogenic Shock, Valvular heart Disease, Congestive Cardiac Failure and Variable Block. Hypertension (26%) and Diabetes Melitus (15%) was the two most common co-existing pathologies, along with Stroke, Respiratory Disease and Renal Disease. 13.5% patients died during their hospital stay. Conclusion: MI as the principal cause of cardiac emergencies is in coherence with other studies done abroad. High prevalence of Hypertention and Ischemic Heart Disease points to the dietery and lifestyle pattern of the people. Improvement of emergency care along with lifestyle modification is essential to minimize the burden of cardiac emergencies in Bangladesh. DOI: http://dx.doi.org/10.3329/bccj.v1i1.14361 Bangladesh Crit Care J March 2013; 1: 23-26